Asystole caused by Hydroxycut Hardcore: A case report and literature review. Issue 3 (27th June 2017) - Zaidan, Julie; Tabet, Rabih; Karam, Boutros; Daneshvar, Farshid; Raza, Mohammed; Bekheit, Soad
Abstract : Obesity is a rising epidemic worldwide driving people to search for remedy through nonconventional therapies. Hydroxycut products are popular supplements used as weight loss aids. Many reports revealed serious adverse effects related to their ingestion. We report the case of a 37‐year‐old healthy male patient who presented following an episode of syncope. On telemetry, he manifested recurrent sinus node arrests, including a symptomatic 24 s sinus pause. The patient admitted to taking Hydroxycut Hardcore for 10 days previously. After discontinuation of the drug, his symptoms completely resolved. This is the first case of Hydroxycut‐associated syncope secondary to bradyarrhythmia.